2012
DOI: 10.1111/j.1751-1097.2012.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Mechanisms induced by a Combination of Hypericin and a Chlorin Based‐Photosensitizer in Head and Neck Squamous Cell Carcinoma Cells

Abstract: The aim of this study was to elucidate photodynamic therapy (PDT) effects mediated by hypericin and a liposomal meso-tetrahydroxyphenyl chlorin (mTHPC) derivative, with focus on their 1:1 mixture, on head and neck squamous cell carcinoma cell lines. Absorption, excitation and photobleaching were monitored using fluorescence spectrometry, showing the same spectral patterns for the mixture as measured for single photosensitizers. In the mixture mTHPC showed a prolonged photo-stability. Singlet oxygen yield for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Thus, our findings are in good agreement with the results in BAECs [40]. The mechanisms underlying Hyp dark toxicity are not well understood [5,41,42], but one possibility may be that Hyp accumulated in mitochondria interacts with members of the Bcl2 family and that in turn results in an increase of apoptotic cells.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Thus, our findings are in good agreement with the results in BAECs [40]. The mechanisms underlying Hyp dark toxicity are not well understood [5,41,42], but one possibility may be that Hyp accumulated in mitochondria interacts with members of the Bcl2 family and that in turn results in an increase of apoptotic cells.…”
Section: Discussionsupporting
confidence: 94%
“…This was an unexpected finding, because Hyp itself has been reported to display low-dark toxicity in many cell lines [4,12]. However, recently evidence emerged that showed similar dark cytotoxicity in malignant cells [5], and there are contradictory results regarding Hyp dark toxicity also in endothelial cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a previous study we have shown that this is perfectly feasible and may be advantageous to detect (subtle) differences between effects of treatment regimes [24]. With the aim to preserve some morphology and avoid complete RNA degradation [25, 26] for our microscopic and RNA studies, we furthermore had to reduce the illumination time from 20 to 1 min.…”
Section: Discussionmentioning
confidence: 99%